Insider trading regulation: to be or not to be? - Adetoun, Adedurotiivii Omowunmi (Centre for Law and Society, 2026)
Insider trading1 may be defined as the act of trading in company securities by persons often referred to as insiders who by virtue of their relationship to the company, possess some information, not available to the public, but material to the securities concerned. For instance, insider trading occurs where a director knows that a company is in a bad financial state and sells his shares in it knowing that in a few days, a cut in the dividend payment will be made public. Likewise, the director will be an insider trader if on being informed before it was generally made public that the company has discovered oil on its own land, he buys more shares in the company with the hope of an increase in their market value as soon as the information is made public.